Anisotropic super-hardness of hexagonal WB2±z thin films. Issue 2 (1st February 2022) - Fuger, C.; Hahn, R.; Zauner, L.; Wojcik, T.; Weiss, M.; Limbeck, A.; Hunold, O.; Polcik, P.; Riedl, H.
Abstract : Transition metal diboride-based thin films are promising candidates to replace state-of-the-art protective and functional coating materials due to their unique properties. Here, we focus on hexagonal WB 2-z, showing that the AlB 2 structure is stabilized by B vacancies exhibiting its energetic minima at sub-stoichiometric WB 1.5 . Nanoindentation reveals super-hardness of 0001 oriented α-WB 2-z coatings, linearly decreasing by more than 15 GPa with predominant 10 1 ¯ 1 orientation. This anisotropy is attributed to differences in the generalized stacking fault energy of basal and pyramidal slip systems, highlighting the feasibility of tuning mechanical properties by crystallographic orientation relations. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: First report of an anisotropic elastoplastic behaviour in super-hard PVD AlB 2 structured WB 2-z . Theoretical and experimental verification of thermodynamically most stable sub-stoichiometric α-WB 2-z coatings by structural and mechanical analysis.